Ancient Greek as a Language for Specific Purposes in Education of Teachers of Theology - Jelena B. Femić Kasapis (University of Belgrade, Teacher Education Faculty, 2019)
The main goal of the paper is to improve the teaching of the Ancient Greek Language through the improvement of the core course syllabuses. The paper focuses on an analysis of the existing syllabuses for the Ancient Greek Language for students of the Faculty of Orthodox Theology of the University of Belgrade, future teachers of theology, by emphasizing the importance of knowing theological terminology. The selected example is the term "ikona" (gr. εἰκών [ikón] - "image"). Descriptive, historical-comparative and contrastive methods were used in our philological analysis, including the necessary method of semantic analysis, in order to clarify the conceptual content of the term. The first hypothesis, based on the author's experience in teaching Ancient Greek, is that the knowledge of terminological paradigms of the Greek language stimulates and develops students' creative power to make correlations and to understand the comprehensiveness of the ideas contained in the New Testament, the ideas that one day they will have to convey to their own students. The second hypothesis is that language analysis and understanding the chapters of the New Testament in its original language create a very important feeling of closeness and familiarity with the language expression of the time of Our Lord Jesus Christ and his apostles. The paper aims to demonstrate the importance and significance of knowing professional theological language and terminology in Ancient Greek for developing theology students' professional competencies. By improving the AncientGreek course syllabus, future theology teachers would not only bridge the time distance between them and the original source, but would also gain a deeper insight into the comprehensive content and original meaning of Christian messages that they will convey to future young generations one day.